Parents' satisfaction of care in medical pediatric ward at Hospital Universiti Sains Malaysia (HUSM) - Aziz, Norelessa Abdul (Universiti Sains Malaysia, 2009)
Patient satisfaction is a component of health care quality and is increasingly being used in many countries in the world. It is because of its role in quality assurance and continuous quality improvement systems. Views of parents take on increased importance because children are too young to express their own judgment to evaluate the health care services. This quantitative study was conducted to explore the level of parents' satisfaction of care in medical pediatric ward at Hospital Universiti Sains Malaysia (HUSM). This research is a cross-sectional, descriptive study using self-administer questionnaire. A total of 45 parents were recruited using purposive sampling from medical pediatric ward, HUSM. The questionnaire consists of two parts: parts A consists of parents' demographic and child health-related data, parts B consists of 47 items of quality of care. Data was analyzed using Statistical Package for Social Science (SPSS) version 12 software. Findings show that four relative higher satisfaction score noted in staff work environment, followed by staff attitudes, caring process, and medical treatment. Whereas accessibility, information illness, information routines, and participation were in lower score relatively. Findings also shows that, there was no significant mean different between parents' satisfaction score with education level (p = 0.058) and frequency of child hospitalization category (p = 0.745). Based on the result, can be conclude that the less satisfied services need to be emphasized and suitable actions should be implemented. This will help to increase the quality of patient care in medical pediatric ward, HUSM.